Gender Differences in Executive Compensation and Job Mobility - Gayle, George-Levi; Golan, Limor; Miller, Robert A. (Journal of Labor Economics, 2012)
Fewer women than men become executive managers. They earn less over their careers, hold more junior positions, and exit the occupation at a faster rate. We compiled a large panel data set on executives and formed a career hierarchy to analyze mobility and compensation. We find, controlling for executive rank and background, that women earn higher compensation than men, experience more income uncertainty, and are promoted more quickly. Among survivors, being female increases the chance of becoming chief executive officer. The unconditional gender pay gap and job-rank differences are primarily attributable to female executives exiting the occupation at higher rates than men.